Effect of post weld heat treatment and TiAlSiN coating on the tensile strength of autogenous plasma arc welding of duplex/ super austenitic stainless steels. (February 2019) - Selvabharathi, R.
Abstract: The present study shows the effect of post weld heat treatment (PWHT) and TiAlSiN coating on tensile, bending strength, hardness and corrosion of Duplex Stainless Steel (DSS) and Super Austenite Stainless Steel (SASS) joined materials in plasma arc welding. Direct aging PWHT process was conducted for 32 h at 918 °C on DSS - SASS materials. The hardness value reduced at the heat affected zone of PWHT samples due to the formation of pentagonal and hexagonal precipitates. TiAlSiN coating was applied in dissimilar material at 450 °C by Physical Vapor Deposition (PVD) process with pressure 3.0 × 10 −3 Pa. In case of TiAlSiN coated sample, the tensile failures occurred at the SASS where as in case of DSS - SASS, PWHT the tensile failure occurred at the fusion zone. This investigation also showed the exhaustive mechanical property relationships of Autogeneous Plasma Arc (A-PA) weldments conducted on the fusion zone based on the process of DSS - SASS, PWHT and TiAlSiN coating by employing scanning electron microscopy, X-ray diffractometry and transmission electron microscopy techniques. Potentio dynamic polarization studies were carried out on both dissimilar and coated samples in 3.5% NaCl solution environment and the results showed that the corrosion resistance of coated samples was improved. When compared with DSS - SASS and PWHT samples, the absence of CrN in TiAlSiN coated materials resulted in high tensile strength and an increase in elongation at fracture surface compared to the coated samples.